Rural Rites in Ovid’s Fasti - Hirt, Maria (ARYS. Antigüedad: Religiones y Sociedades, 2020)
This paper analyzes the presentation of rural festivals in Ovid’s Fasti using the concept of lived ancient religion and especially the idea of individual appropriation of religious norms, actions and beliefs. As a literary work, the Fasti draw on material from other Augustan poets and appropriate it to the composition of the work and especially to the context of the Roman festival calendar. In the case of the rural festivals that are presented in the Fasti, this appropriation can be seen for example in the treatment of the importance of peace for rural life. In the Fasti, the idealized rural scenes are not an object of the speaker’s desire as they are for example in Tibullus’ elegies. Instead, the described peace is identified as the Pax Augusta and the speaker utters thanks to the emperor who makes it possible that the celebrating rustics can enjoy this peace. Thus, the rural festivals are connected to urban politics and to the urban festival calendar. In the Fasti, the rural and urban festival communities do not exist isolated from each other as they share the same conditions (the Pax Augusta) and emotions (joy and gratitude) and thus form an emotional community.